Genetic plasticity of the Shigella virulence plasmid is mediated by intra- and inter-molecular events between insertion sequences - Pilla, G; McVicker, G; Tang, C (Public Library of Science, 2017)
Acquisition of a single copy, large virulence plasmid, pINV, led to the emergence of Shigella spp. from Escherichia coli. The plasmid encodes a Type III secretion system (T3SS) on a 30 kb pathogenicity island (PAI), and is maintained in a bacterial population through a series of toxin:antitoxin (TA) systems which mediate post-segregational killing (PSK). The T3SS imposes a significant cost on the bacterium, and strains which have lost the plasmid and/or genes encoding the T3SS grow faster than wild-type strains in the laboratory, and fail to bind the indicator dye Congo Red (CR). Our aim was to define the molecular events in Shigella flexneri that cause loss of Type III secretion (T3S), and to examine whether TA systems exert positional effects on pINV. During growth at 37ÊC, we found that deletions of regions of the plasmid including the PAI lead to the emergence of CR-negative colonies; deletions occur through intra-molecular recombination events between insertion sequences (ISs) flanking the PAI. Furthermore, by repositioning MvpAT (which belongs to the VapBC family of TA systems) near the PAI, we demonstrate that the location of this TA system alters the rearrangements that lead to loss of T3S, indicating that MvpAT acts both globally (by reducing loss of pINV through PSK) as well as locally (by preventing loss of adjacent sequences). During growth at environmental temperatures, we show for the first time that pINV spontaneously integrates into different sites in the chromosome, and this is mediated by inter-molecular events involving IS1294. Integration leads to reduced PAI gene expression and impaired secretion through the T3SS, while excision of pINV from the chromosome restores T3SS function. Therefore, pINV integration provides a reversible mechanism for Shigella to circumvent the metabolic burden imposed by pINV. Intra- and inter-molecular events between ISs, which are abundant in Shigella spp., mediate plasticity of S. flexneri pINV.